2017
DOI: 10.1246/bcsj.20170153
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Bridged Polysilsesquioxane Membranes from Bis[3-(triethoxysilyl)propyl]amine for Water Desalination

Abstract: Bridged polysilsesquioxane membranes containing amine units were prepared from bis [3-(triethoxysilyl)propyl]amine (BTESPA) by a sol-gel process, which consisted of sol formation by hydrolysis/condensation polymerization of BTESPA under neutral conditions and calcination of cast films of the sols on sulfonated polyethersulfone support membrane. A similar treatment of BTESPA, including sol formation under acidic conditions, afforded membrane with ammonium units. Thus-obtained porous BTESPA-based membrane was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Considering these backgrounds, we reported a reverse osmosis (RO) membrane based on bridged polysilsesquioxane for water purification. 35 The rigidity of the organic bridging spacer increased the membrane pore size, and RO membranes prepared from bis(triethoxysilyl)ethane, -ethene, and -ethyne showed improved water permeability as the rigidity of the bridging units increased in the order ethane <ethene <ethyne. Bridged polysilsesquioxanes are promising materials for thermal insulation because the organic bridging spacer provides porosity and the polysilsesquioxane framework enhances the mechanical strength and the thermal property.…”
Section: ■ Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering these backgrounds, we reported a reverse osmosis (RO) membrane based on bridged polysilsesquioxane for water purification. 35 The rigidity of the organic bridging spacer increased the membrane pore size, and RO membranes prepared from bis(triethoxysilyl)ethane, -ethene, and -ethyne showed improved water permeability as the rigidity of the bridging units increased in the order ethane <ethene <ethyne. Bridged polysilsesquioxanes are promising materials for thermal insulation because the organic bridging spacer provides porosity and the polysilsesquioxane framework enhances the mechanical strength and the thermal property.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Bridged polysilsesquioxanes are promising materials for thermal insulation because the organic bridging spacer provides porosity and the polysilsesquioxane framework enhances the mechanical strength and the thermal property. 26,35,36 We previously reported the preparation of bridged polysilsesquioxane by the nitrogen flow method, 37 and the molecular weight of ethylene-bridged polysilsesquioxane was controlled by changing the amount of water, according to a reported procedure. 37−40 A gel film of ethylene-bridged polysilsesquioxane was obtained by heating at 80 °C for a week.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] To date, we have applied bridged PSQ to reverse osmosis (RO) membrane for water purication. 20 Interestingly, water permeability was improved depending on the rigidity of the bridged spacer; namely, the membrane pore size increased by the rigidity of the bridged spacer. Based on these ndings, we have expected that bridged structure provides porosity, resulting in an excellent thermal insulator property.…”
Section: Introductionmentioning
confidence: 99%
“…[6] We have been studying polysilsesquioxane (PSQ)-based RO membranes that show high mechanical and thermal stability and resistance to chlorine relative to polyamide-RO membranes. [7,8] The membranes are usually prepared by the hydrolysis/condensation polymerization of alkoxysilane precursors using the sol-gel process or interfacial polymerization. Some of the precursors for RO membrane preparation used in previous studies and the present work are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%